Meta Analysis: Reciprocal Teaching Learning Model to Improve Mathematics Learning Outcomes - Ulfiyati, Ulya; Scolastika, Mariani; Mariani, Isnaini Rosyida; Pujiastuti, Emi; Mulyono, Mulyono (Universitas Teknokrat Indonesia, 2025)
The success of an education is associated with the high and low learning outcomes that have been achieved. The results of mathematics learning are very important, because they measure whether the learning that has been carried out so far has been successful or not. One learning model to improve mathematics learning outcomes is the reciprocal teaching learning model. The aim of this research is to analyze articles on the topic of mathematics learning outcomes in the reciprocal teaching model. The method used in this research is the meta analysis method. The research obtained results that there were three articles with effect sizes in the medium category and three articles with effect sizes in the strong category. The average effect size value of the six articles analyzed was 1.27 in the strong category. So it shows that the reciprocal teaching learning model has a strong influence in improving students' mathematics learning outcomes. Apart from that, the results of hypothesis testing were carried out using the t test, namely t test = 10.89 > 1,968 = t table. This shows that the average mathematics learning outcomes of students using the reciprocal teaching learning model are better than the average mathematics learning outcomes of students using the conventional learning model.